UK temporomandibular joint replacement database: a report on one-year outcomes. Issue 9 (November 2017) - Elledge, R.; Attard, A.; Green, J.; Lowe, D.; Rogers, S.N.; Sidebottom, A.J.; Speculand, B.
Abstract: Alloplastic temporomandibular joint (TMJ) replacements are increasingly subspecialised, and supraregional centres that treat sufficient numbers to ensure high standards are emerging. Having recently reported the introduction of a national TMJ joint replacement database that is endorsed by the British Association of TMJ Surgeons (BATS), we now present the first-year outcomes. This was a review of all data in the BATS National Case Registration of TMJ Replacement as of June 2014. A total of 252 one-year outcome records were available. Key outcomes were median (IQR) improvements in interincisal distance of 9 (4–15) mm (p < 0.001) and worst-sided pain score of 6 (4–8) (p < 0.001). Pain scores improved or remained static at one year in all but 3 (2%) patients. There was a significant improvement in the proportion of patients who reported a good, very good, or outstanding quality of life at one year (38% at baseline to 87% at one year; p < 0.001). While outcome reports from single centres for alloplastic TMJ replacements have already been published in the United Kingdom, this is the first dedicated national database in this country that will yield valuable longitudinal follow-up data. Outcomes were comparable with smaller published series and showed improvements in pain, dietary intake, quality of life, and function, with few outliers. The database has recently moved to a new software system and we hope to publish three-year and five-year outcomes in due course.